Principles of Islamic Criminal Law in the Perspective of Jinayah Fiqh - Dinda Suciana Rambe; Hanisah Raihanah Larosa; Elis S Masita Damanik (Jurnal Sahabat ISNU SU, 2024)
This study explains that Islamic criminal law or fiqh jinayah is an important part of the Islamic legal system that aims to maintain order, justice, and the welfare of the community. In its application, Islamic criminal law is not only oriented towards imposing sanctions, but also emphasizes the protection of human rights, justice, and the balance between individual and societal interests. This study aims to understand the principles of Islamic criminal law and to identify the various principles that form the basis for the application of fiqh jinayah. The research method used is normative legal research with a library approach, through a study of the Qur'an, Hadith, books, and relevant scientific journals. The results of the study indicate that the principles of Islamic criminal law include the principle of legality, the principle of prohibition of retroactive application, the principle of presumption of innocence, the principle of personal responsibility, the principle of justice and equality before the law, the principle of forgiveness and peace, the principle of protection of human rights, and the principle of humanity in the implementation of punishment. These principles indicate that Islamic criminal law has principles of justice that are in line with modern legal values ​​and aim to create the welfare of the community.